Pembuatan Indeks Kaset Berbasis Web Aplication pada Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Rahmadhani, Rahmadhani; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper disscussed about making the cassette index based on web aplication at Dinas Kearsipan dan Perpustakaan in province of West Sumatera. The puspose of this study to describe the process making the index by using PHP’s program (Hypertext Prepeccssor) based web aplication. The data is collected through observations and interviews with officers the Dinas Kearsipan dan Perpustakaan in province of West Sumatera. Analyzing the dateis done descriptively, it describes the findings and researches data according to the reserch at Dinas Kearsipan dan Perpustakaan in province of West Sumatera.Keywords: index, cassette, web aplication